Selenium concentration in cattle serum and fodder from two areas in Ethiopia with contrasting human selenium concentration - Hailu, K.; Gashu, D.; Joy, E.J.M.; Alonso, Silvia; Gizaw, Solomon; Gameda, S.; Ander, E.L.; Bailey, E.H.; Wilson, L.; Lark, R.M.; Kumssa, D.B.; Broadley, M.R. (IMR Press, 2022)
Introduction: Selenium (Se) is an essential mineral for livestock health and productivity. In cattle, Se deficiency is associated with delayed conception, growth retardation, and increased morbidity and mortality. Methods: We conducted a survey of cattle serum (n = 224) and feed (n = 81) samples from two areas with contrasting human and cereal grain Se concentration in Ethiopia. The fodder samples include stover, straw, hay and pasture grass. Se concentration of the samples were measured using inductively coupled plasma-mass spectrometry. Results: Serum Se concentration ranged from 14.9 to 167.8 μg/L (median, 41.4 μg/L). Cattle from East Amhara had significantly greater serum Se concentration compared to cattle from West Amhara (median: 68.4 μg/ L vs 25.7 μg/ L; p < 0.001). Overall, 79.8% of cattle had Se deficiency (< 81 μg/L). All of the cattle from West Amhara were Se deficient compared with 62.5% of those from East Amhara. State of lactation of cows or age of cattle was not associated with serum Se concentration. The Se concentrations of feed samples ranged from 0.05 to 269.3 μg/kg. Feed samples from East Amhara had greater Se concentration than samples from West Amhara. Cow serum and cattle feed Se concentrations showed strong spatially correlated variation, with a strong trend from East to West Amhara. Conclusions: This study shows that cattle Se deficiency is likely to be highly prevalent in Ethiopia, which will negatively affect the health and productivity of livestock. The deficiency appears to be geographical dependent. More extensive surveys to map Se concentration in soil-feed-livestock-human cycle are required in Ethiopia and elsewhere.